Pendampingan Pastoral yang Memberdayakan Penyintas Sinabung yang Mengalami Trauma - Indah Sriulina (Asosiasi Teolog Indonesia, 2016)
Hidden trauma within the survivors of an erupting Mount Sinabung has made it difficult for survivors to think objectively about the future—a limitation that has